Imitation promotes affiliation in infant macaques at risk for impaired social behaviors. Issue 4 (16th September 2014) - Sclafani, Valentina; Paukner, Annika; Suomi, Stephen J.; Ferrari, Pier F.
Abstract Parental responsiveness and synchronization during early face‐to‐face interactions between mother and infant have been theorized to affect a broad spectrum of positive developmental outcomes in social and cognitive infant growth and to facilitate the development of a sense of self in the baby. Here we show that being imitated can significantly affect the behavior of nursery‐reared infant monkeys, which are at an increased risk for developing aberrant social behaviors. Infants look longer and lipsmack more at an experimenter both during imitation and after being imitated. These results demonstrate that from early in life imitation might be used as a privileged form of communication by adults to enhance infants' visual engagement and their social communication. Imitation may therefore be useful to counteract the negative effects of early social adversities.